Impact of Patient Characteristics on the Outcomes of Patients with Gastrointestinal Cancers Treated with Immune Checkpoint Inhibitors - Hyejee Ohm; Omar Abdel-Rahman (Current Oncology, 2023)
Gastrointestinal (GI) cancers are a group of malignancies that globally account for a significant portion of cancer incidence and cancer-related death. Survival outcomes for esophageal, gastric, pancreatic, and hepatobiliary cancers remain poor, but new treatment paradigms are emerging with the advent of immune checkpoint inhibitor (ICI) therapy. This review characterizes patient-related prognostic factors that influence the response to ICI therapy. We performed an analysis of the landmark randomized clinical trials in esophageal, gastric, colorectal, hepatocellular, pancreatic, and biliary tract cancers in terms of patient demographic factors. A literature review of smaller retrospective studies investigating patient-related factors was completed. The immunological bases for these associations were further explored. The key predictive factors identified include age, sex, performance status, geography, body mass index, sarcopenia, gut microbiome, various biochemical factors, and disease distribution.